KESIAPAN DOSEN AKUNTANSI DALAM MENGINTEGRASIKAN MATERI IFRS DALAM MATA KULIAH (Fokus Ekonomi, 2011)
This research’s goal is to describe current coverage status of course material pertaining toInternational Financial Reporting Standards (IFRS) in financial accounting course, accountinglecturer’s readiness to integrate IFRS into their course, and institutional support to their lecturers tointegrate IFRS into their course. This research also examines impact of accounting lecturer’sreadiness and institutional support on IFRS coverage, and explores perceived implication of IFRSadoption on accounting practice and accounting education. Data collected through survey. Weconducted a survey on 53 accounting lectures from 14 universities in Yogyakarta. The result showthat on integrating the IFRS material in the accounting courses, the IFRS coverage’s mean, theaccounting lecture’s readiness, and the institutional support is relatively low. A regression analysisreveals that accounting lecture’s readiness is positively affect the IFRS coverage at significant levelof 1%, while institutional support is not statistically significant. Results also indicate 72% oflecturers’ perceive IFRS will increase judgment on the implementation, while 51% of surveyedlecturers suggest some adjustment on current curriculum, and 68% believe that professional ethicsshould be included in future curriculum.Key words: IFRS coverage, accounting lecture’s readiness, institutional support.